Effect of Ticagrelor versus Clopidogrel on Oxidative Stress Bio-markers in Patients with Chronic Stable Angina after Percutaneous Coronary Intervention (Cardiovascular Journal, 2017)
Background: Ticagrelor, a reversible P2Y12 receptor inhibitor may represent a significant advancement over currently available oral antiplatelet drugs in treatment of ischaemic heart disease.The study was intended to compare the effect of Ticagrelor and Clopidogrel on oxidative stress markers in patients of chronic stable angina (CSA) following percutaneous coronary intervention (PCI).Methods: The study included a total of 100 CSA patients. Patients were divided into two groups, Ticagrelor and Clopidogrel treated groups (each having 50 patients). The baseline laboratory parameters-Malondihyde (MDA), Reduced glutathione (GSH), bleeding time, clotting time and platelet count, were measured and then patients of both groups underwent PCI. The same parameters were again assessed at follow up after 4 weeks of intervention. Comparisons of the laboratory parameters were made between two groups at baseline and at follow up and also within group before and after intervention.Results: The level of plasma MDA in Ticagrelor group was significantly reduced from baseline to follow up(4.5 ± 1.8 to 1.4 ± 0.7, p